Perilaku Pro Lingkungan pada Pengurus Organisasi Mahasiswa Pecinta Alam - Putra, Randy Pramana (Fakultas Psikologi, 2019)
The current state of the environment is getting worse and therefore required a solution to these problems, environmental problems that occur are a result of human behavior, for the solution also is of human behavior is referred to as pro-environmental behavior. However, members of the student nature lovers college (Mapala) is supposed to be a model for the younger generation to be more concerned about the environment in daily activity still smoke, wear disposable plastic and Mapala work program centered on adventure activities outdoors does not represent the pro-environmental behavior. The purpose of this study was to describe the pro-environmental behavior onboard members Mapala using statistical approach descriptive The study included 77 daily Mapala committee consisting of DIMPA Malang Muhammadiyah University of Malang, IMPALA Brawijaya University, Malang State University Jonggring Salaka, and Tursina State Islamic University of Maulana Malik Ibrahim using total technique sampling. collection data using a scale of General ecological behavior scale (GEBS ). The result showed that Mapala organization committee, who has a high environmental behavior category as many as 41 people (53.2%) and the lowest is 36 people (46.8%).